(3GdJHjjf hGdEjVGMs - (3eMeO Hf HjQ Ydj Hf EScfOQ GdHQcdj GdQhej , eMjj GdOjf, J (B981 (3g` s ((3eOQSI GdSdWGf eMeO NGf HGdbSWfWjfI s)
(3ChdgG (B:s
(3hHYO, agPg cdeGJ SejJgG GdJHjjf hGdEjVGM dchfgG HjGfkG hEjVGMkG deYGfj hCdaGX ef GdYhGed GdLOjOI ddTjN s
(3BNQgG (B:s
(3dG jCJj GdNHQ EdG ef LgJg dHGA eJYdb Hbhdg QH, hGdeYfi Ef ceGd GdJYXje hfgGjI GdJaNje ChdkG hBNQkG ddg s
(3hgPG GdcJGH gh TQM GdYhGed GdfMhjI deMeO Hf HjQ Ydj GdHQcdj GdQhej GdeJhai (B981(3g``s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs